CHALLENGES TO THE PRESERVATION/RECONSTRUCTION OF DEMOCRACY IN BRAZIL - Machado, Rebel Zambrano (Seven Editora, 2025)
This article discusses democracy and the importance of political parties in the process of preserving/reconstructing democracy in Brazil, as well as our ephemeral exercise of citizenship, which presents itself as a passive subject of rights in an alienated and cowardly society. It emphasizes dilemmas for preserving/reconstructing Brazilian democracy and identifies fragile social participation as one of its main challenges. This article focuses on partial results of research conducted using the critical dialectical method and Gramscian categories, based on bibliographical research in doctrinal and legal sources, both physical and digital.DOI: https://doi.org/10.56238/sevened2025.029-036